Evaluation of In Vitro Cytotoxic and Apoptotic Effects of Miltefosine on the Toxoplasma gondii RH Strain - Shahram Khademvatan; Elham Yousefi; Negar Asadi; Esmaeil Abasi (Iranian Journal of Parasitology, 2024)
Background: We aimed to investigate the cytotoxic and apoptotic effects of miltefosine on Toxoplasma gondii RH strain by various techniques.